Assisting Decision-Making on Age of Neutering for Mixed Breed Dogs of Five Weight Categories: Associated Joint Disorders and Cancers - Hart, Benjamin L.; Hart, Lynette A.; Thigpen, Abigail P.; Willits, Neil H. (Frontiers in Veterinary Science, 2020)
The early neutering of male and female dogs and its relationship to an increased risk of joint disorders and some cancers has recently become a concern, raising questions about the standard practice in the U.S. and much of Europe of neutering by 6 months of age. A noteworthy recent finding from this center is that there are major breed differences with small-dog breeds generally showing little vulnerability to neutering compared with breeds of larger body size. These findings on purebreds raise questions for dog owners and veterinarians about mixed-breed dogs. The purpose of this study was to examine a sample of mixed breed dogs of five weight categories using the same veterinary hospital database and diagnostic criteria for joint disorders and cancers as used in the newly published paper on 35 breeds and previous papers on the Golden Retriever, Labrador Retriever, and German Shepherd Dog. The weight categories were <10 kg (739 cases), 10–19 kg (546 cases), 20–29 kg (992 cases), 30–39 kg (604 cases), and over 40 kg (258 cases). Males and females were analyzed separately, as were various ages at neutering. The joint disorders examined were hip dysplasia, cranial cruciate ligament tear or rupture, and elbow dysplasia. The cancers were lymphoma, mast cell tumor, hemangiosarcoma, and osteosarcoma. There was no significant increased occurrence of one or more cancers, compared with intact dogs, in any weight category. However, in the three categories of dogs weighing 20 kg or more, neutering before 1 year generally was significantly associated with risks of one or more joint disorders above that of dogs left intact, commonly to 3 times the level of intact dogs, with sex differences in the degrees of joint disorders associated with neutering. For the dogs in the two weight categories <20 kg, no increased risks were found for joint disorders. This information can be useful to dog caregivers in deciding on the age at which to neuter specific dogs, and for veterinarians offering guidance to pet owners.